An Inter-University CBL Course and Its Reception by the Student Body: Reflections and Lessons Learned (in Times of COVID-19) - De Stefani, Paolo; Han, Ling (Frontiers in Education, 2022)
The COVID-19 pandemic and the consequent restrictive measures adopted by the countries have significantly reduced the capacity of higher education institutions to carry out innovative international teaching and learning activities. This paper provides a short reconstruction of how the seven European universities, members of the Arqus Alliance, handled this challenge. During 2020-21, that is, in full pandemic, the Arqus partners redesigned and implemented a trans-European challenge-based learning (CBL) project involving university students from many disciplinary fields, including social sciences and humanities, focused on climate change-related risks in European cities and areas. Based on this experience, a contingent conceptualization of CBL is proposed, comprising eight characteristics, whose effectiveness is then tested against data provided by students who participated in the courses. In this context, the results of a Likert questionnaire submitted to students from participating universities will be discussed. The analysis is meant to provide a deeper understanding of CBL not only as a pedagogical tool for a specific output, but also as a broader learning experience generating outcomes for teachers who plan and deliver CBL activities, and for the beneficiaries of such activities. In other words, the article aims to highlight some enabling and inhibiting factors of 'strategic CBL' - this latter expression is supposed to capture the process of designing and implementing a CBL activity as a CBL practice in itself.